Volatilidade dos retornos dos índices de energias renováveis e choques de incertezas nos Estados Unidos e União Europeia - Souza, Alexandre Gomes (2021)
The goal of this work is to estimate the volatility of returns and shocks of uncertainties on the indices related to the performance of the renewable energy market in the USA and Europe. In this sense, an analysis of the risks associated with the European Renewable Energy and Renewable Energy Generation indexes can reveal how they affect the sector’s performance. First, structural break tests will be estimated on the return trajectories and check if the analysis should be divided between regimes. To estimate volatility, conditional heteroscedastic models proposed in the literature will be used, particularly the Dynamic conditional correlation multivariate GARCH (DCC-MGARCH). The data were chosen based on the Standard & Poor’s 500, WilderHill, Arca Tech 100, West Texas Intermediate and Morgan Stanley Capital International, Thomson Reuters/ CoreCommodity and U.S. Dollar indices. In addition to the estimates of all parameters, quasi-correlation matrices, quasi covariance, and uncertainties shocks over the studied indices will be obtained through impulse response functions obtained by a VAR model.